(3GdeNJGQ ef efGbH GdCNjGQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eMeO Hf YeQ Hf GdMSjf s)
(3ChdgG (B:s
(3JQLeI YHO GdQMef Hf YeQh GdChRGYi s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3GdehLhO efg GdfUa GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B358 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B234 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1623s
Keywords: (3GdJGQjNs